Review of Thermal Properties of Snow, Ice and Sea Ice - Yen,Yin-Chao (1981)
This treatise thoroughly reviews the subjects of density, thermal expansion and compressibility of ice; snow density change attributed to destructive, constructive and melt metamorphism; and the physics of regelation and the effects on penetration rate of both the thermal properties of the wire and stress level. Heat capacity, latent heat of fusion and thermal conductivity of ice and snow over a wide range of temperatures were analyzed with regression techniques. In the case of snow, the effect of density was also evaluated. The contribution of vapor diffusion to heat transfer through snow under both natural and forced convective conditions was assessed. Expressions representing specific and latent heat of sea ice in terms of sea ice salinity and temperature were given. Theoretical models were given that can predict the thermal conductivities of fresh bubbly ice and sea ice in terms of salinity, temperature and fractional air content. (Author)